Hubungan Antara Dukungan Sosial Teman Sebaya dengan Kesejahteraan Psikologis Mahasiswa Yang Menghadapi Deadline Tugas - Waras Lestari; Aigal Akira (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Assignment deadlines are a common academic demand faced by university students. The volume of assignments requiring completion within a limited timeframe can impact students' psychological well-being. In this context, peer social support provided by individuals sharing similar experiences and situations plays a crucial role. This study aimed to determine whether a relationship exists between peer social support and the psychological well-being of students facing assignment deadlines. The study involved 114 students from Universitas Bhayangkara Jakarta Raya who were dealing with assignment deadlines. A quantitative approach utilizing a correlational research design was employed. The results revealed a significant positive correlation between peer social support and psychological well-being among students facing assignment deadlines (r = 0.591; p = 0.001), leading to the conclusion that the alternative hypothesis (Ha) was accepted. These findings indicate that higher levels of peer social support are associated with higher levels of psychological well-being, whereas lower levels of peer social support are associated with lower psychological well-being.